Prevalence, types, distribution and associations of psychosocial problems among university students in Uganda - Nsereko, Norman David; Musisi, Seggane; Nakigudde, Janet; Holtzman, Steven (International Journal of Research Studies in Psychology, 2014)
The prevalence of psychosocial problems and their associations among University students in Uganda has received very little research attention. Yet, this information is important to provide data to assist in mental health policy formulation for counseling intervention among the vulnerable university students populations in Uganda. The study objective was to investigate the prevalence, types, distribution and associations of psychosocial problems among university students in Uganda. It was part of a larger PhD study that validated an instrument for assessing university students’ psychosocial problems in Uganda. This study employed a descriptive cross sectional survey technique. Five universities participated in a survey conducted during the 2012/13 academic year. Out of 1101 approached students, 976 (88.6%) completed the survey which included a socio-demographic questionnaire, study program characteristics, medical health questionnaire and the University Students Evaluation of Psychosocial Problems (USEPP) instrument which was used to evaluate the psychosocial problems. The prevalence, types and distribution of psychosocial problems among the students was established using descriptive statistics and regression analysis established the relationship between psychosocial problems and the correlates of interest. The estimated prevalence of psychosocial problems among the university students was 36.5%. Students living in off- campus hostels, having chronic medical conditions, and those with a previous history of mental health problems and who perceived their health as poor/fair were at a higher risk of psychosocial problems. These findings highlight to the need to initiate policies to address the students’ psychosocial problems.
Keywords: Prevalence; Psychosocial problems; University students; Social demographics; Counselling intervention